Associations between obesogenic risk and depressive symptomatology in Australian adolescents: a cross-sectional study. Issue 8 (7th April 2014) - Hoare, E; Millar, L; Fuller-Tyszkiewicz, M; Skouteris, H; Nichols, M; Jacka, F; Swinburn, B; Chikwendu, C; Allender, S
Abstract : Background: Depression and obesity are significant health concerns currently facing adolescents worldwide. This paper investigates the associations between obesity and related risk behaviours and depressive symptomatology in an Australian adolescent population. Methods: Data from the Australian Capital Territory It's Your Move project, an Australian community-based intervention project were used. In 2012, 800 students (440 females, 360 males) aged 11–14 years (M=13.11 years, SD=0.62 years), from 6 secondary schools were weighed and measured and completed a questionnaire which included physical activity, sedentary behaviour and dietary intake. Weight status was defined by WHO criteria. A cut-off score ≥10 on the Short Mood and Feelings Questionnaire indicated symptomatic depression. Logistic regression was used to test associations. Results: After controlling for potential confounders, results showed significantly higher odds of depressive symptomatology in males (OR=1.22, p<0.05) and females (OR=1.12, p<0.05) who exceeded guidelines for daily screen-time leisure sedentary activities. Higher odds of depressive symptoms were seen in females who consumed greater amounts of sweet drink (OR=1.18, p<0.05), compared to lower female consumers of sweet drinks, and males who were overweight/obese also had greater odds of depressive symptoms (OR=1.83, p<0.05) compared to male normal weight adolescents. Conclusions: This study demonstrates the associations between obesogenic risks and depression in adolescents. Further research should explore the direction of these associations and identify common determinants of obesity and depression. Mental health outcomes need to be included in the rationale and evaluation for diet and activity interventions.